MicroRNA Let-7i Is a Promising Serum Biomarker for Post-stroke Cognitive Impairment and Alleviated OGD-Induced Cell Damage in vitro by Regulating Bcl-2 - Wang, Zhan-Qiang; Li, Kuo; Huang, Jie; Huo, Tian-Tian; Lv, Pei-Yuan (Frontiers in Neuroscience, 2020)
Background: The mechanism of post-stroke cognitive impairment (PSCI) has not been explained. We aimed to investigate whether miR-let-7i participate in the post-stroke cognitive impairment (PSCI) and illuminate its underlying role in OGD-induced cell apoptosis. Methods: Blood samples from 36 subjects with PSCI and 38 with post-stroke cognitive normality (Non-PSCI) were collected to evaluate the differential expression of miR-let-7 family members, using qRT-PCT analysis. Spearman correlation was performed to estimate the correlation between the miR-1et-7i level and Montreal Cognitive Assessment (MoCA) score. Treatment of SH-SY5Y cells with oxygen glucose deprivation (OGD) was used to induce cell apoptosis in vitro. Effects of miR-let-7i on OGD-induced cell apoptosis was estimated after transfection. The target gene of miR-let-7i was analyzed by dual luciferase reporter gene assay. Results: The expression of miR-let-7i was up-regulated in PSCI patients compared with Non-PSCI (p<0.001) and negatively correlated with MoCA score (r=-0.643, p<0.001). When exposed to OGD, SH-SY5Y cells showed significant apoptosis accompanied by miR-let-7i up-regulation. In OGD-treated cells, miR-let-7i up-regulation was accompanied by cell apoptosis, while down-regulation showed the opposite effect. Luciferase reporter assay showed that Bcl-2 was a target gene of miR-let-7i. Western blot showed that miR-let-7i up-regulation promoted Bcl-2 expression, while qRT-PCR showed that miR-let-7i had no effect on Bcl-2 expression. Conclusions: miR-let-7i was overexpressed in PSCI patients and it could be used as diagnostic biomarker for PSCI. We illuminated the potential mechanism that miR-let-7i alleviated OGD-induced cell damage by targeting Bcl-2 at the post-transcriptional level.